The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1308/rcsann.2016.0007
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic deprivation and age are barriers to the online collection of patient reported outcome measures in orthopaedic patients

Abstract: Introduction Questionnaires are used commonly to assess functional outcome and satisfaction in surgical patients. Although these have in the past been administered through written forms, there is increasing interest in the use of new technology to improve the efficiency of collection. The aim of this study was to assess the availability of internet access for a group of orthopaedic patients and the acceptability of online survey completion. Methods A total of 497 patients attending orthopaedic outpatient clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…In addition, we used an HIV-specific instrument that was developed together with patients and that measures preferences as well as experiences. Furthermore, to reduce potential sampling bias related to online survey research [ 17 ], respondents were provided with the option of filling out a hard copy version of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we used an HIV-specific instrument that was developed together with patients and that measures preferences as well as experiences. Furthermore, to reduce potential sampling bias related to online survey research [ 17 ], respondents were provided with the option of filling out a hard copy version of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…We consider the fact that we have data from all the treatment centres in the country to be a strength of this study. Furthermore, we offered the option of completing out a paper version of the questionnaire, to reduce sampling bias that can occur when collecting patient-reported data online [ 20 ]. Finally, the open-ended nature in which respondents could state their views and concerns provided us with a variety of information that we could not have anticipated had we chosen to offer a limited number of answers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors found 72% of respondents to have internet access, and 40% indicated a preference for outcomes assessments to take place via email or the internet, while the remaining preferred a face-to-face evaluation or standard mail. 13…”
Section: Discussionmentioning
confidence: 99%
“…The administration of electronic PRO surveys via email poses a unique set of obstacles to effective administration and high patient compliance, such as a lack of internet access, outdated email addresses, use of spam/junk mail folders, ease of dismissal, impersonal nature, and risk of survey fatigue. Jenkins et al 13 conducted an investigation in 2016 in which they surveyed 497 patients who presented to an orthopaedic outpatient clinic regarding their accessibility to the internet and preferred means for completing follow-up questionnaires. Interestingly, the authors found 72% of respondents to have internet access, and 40% indicated a preference for outcomes assessments to take place via email or the internet, while the remaining preferred a face-to-face evaluation or standard mail.…”
Section: Discussionmentioning
confidence: 99%